Skeletal muscle development in vertebrate animals - Shahjahan, Md (Asian Journal of Medical and Biological Research, 2015)
This review covers the pre- and post-natal development of skeletal muscle of vertebrate animals with cellular and molecular levels. The formation of skeletal muscle initiates from paraxial mesoderm during embryogenesis of individuals which develops somites and subsequently forms dermomyotome derived myotome to give rise axial musculature. This process (myogenesis) includes stem and progenitor cell maintenance, lineage specification, and terminal differentiation to form myofibrils consequent muscle fibers which control muscle mass and its multiplication. The main factors of muscle growth are proliferation and differentiation of myogenic cells in prenatal stage and also the growth of satellite cells at postnatal stage. There is no net increase in the number of muscle fibers in vertebrate animals after hatch or birth except fish. The development of muscle is characterized by hyperplasia and hypertrophy in prenatal and postnatal stages of individuals, respectively, through Wnt signalling pathway including environment, nutrition, sex, feed, growth and myogenic regulatory factors. Therefore further studies could elucidate new growth related genes, markers and factors to enhance meat production and enrich knowledge on muscle growth. Asian J. Med. Biol. Res. June 2015, 1(2): 139-148